Bem mais que pós-moderno: poder, sociedade civil e democracia na modernidade periférica radicalizada - Marco Aurélio Nogueira (Ciências Sociais Unisinos)
The article reflects freely on the process of radicalization of the modern, focusing on some topics and problems that arise from the objectivation of this process under peripheral conditions. Starting from the hypothesis that radicalized peripheral modernity lives with a dynamic of institutional difficulties and of an organizational suffering that deregulates social practices and blocks the actions of civil society, the text investigates the chances of democratic power in a historical and social situation that seems to be not only breaking apart, but also losing the typical centers of reference, authority and order